2016
DOI: 10.1155/2016/2069290
|View full text |Cite
|
Sign up to set email alerts
|

Serum from Varicose Patients Induces Senescence‐Related Dysfunction of Vascular Endothelium Generating Local and Systemic Proinflammatory Conditions

Abstract: Although the role of endothelium in varicose vein development is indisputable, the effect of the pathology on biological properties of endothelial cells remains unclear. Here we examined if the presence of varicose veins affects senescence of endothelial cells (HUVECs) and, if so, what will be the local and systemic outcome of this effect. Experiments showed that HUVECs subjected to serum from varicose patients display improved proliferation, increased expression of senescence marker, SA-β-Gal, and increased g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…The senescence of myoblast has been associated with muscular dystrophy and with premature muscle wasting occurring in Bmi1 deficient young mice [ 36 ]. Senescence induced by ET-1 at vascular level has been involved in some pathologies [ 37 ], such as diabetes [ 38 ], varicosity [ 39 ] and thrombosis [ 40 ]. So, senescence induced by ET-1 at muscle level could be implicated in the development of fibrosis, exacerbating muscle damage, as the regenerative potential of skeletal muscle declines with age and this impairment is associated with an increase in tissue fibrosis [ 4 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The senescence of myoblast has been associated with muscular dystrophy and with premature muscle wasting occurring in Bmi1 deficient young mice [ 36 ]. Senescence induced by ET-1 at vascular level has been involved in some pathologies [ 37 ], such as diabetes [ 38 ], varicosity [ 39 ] and thrombosis [ 40 ]. So, senescence induced by ET-1 at muscle level could be implicated in the development of fibrosis, exacerbating muscle damage, as the regenerative potential of skeletal muscle declines with age and this impairment is associated with an increase in tissue fibrosis [ 4 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results showed a relationship between oxidative stress and chronic venous insufficiency at the tissue level and the systemic level beginning in the first years of the disease. Mikuła-Pietrasik et al [30] showed that the sera of varicose patients increased cell proliferation, expression of the senescence marker SA- β -Gal, and ROS production in the endothelial cells of human umbilical veins (HUVECs) compared to the sera of healthy individuals. This result suggests that the presence of oxidative stress at a systemic level is the main factor triggering the progression of the pathology.…”
Section: Discussionmentioning
confidence: 99%
“…By providing a baseline level of NO in the vein and neutralizing ROS, it makes sense that patients with low eNOS expression are more susceptible to endothelial deterioration and develop valvular incompetence (venous reflux). The low expression of eNOS may be related to CVI and any disease in which the mechanism involves endothelium dysfunction, as indicated by Mikuła-Pietrasik et al [30]. However, the expression of eNOS in the tunica adventitia suggests that it is reactive and remains functionally active.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies concerning advanced forms of dermal pathology in CVI patients (i.e., dermal fibrosis and venous ulcers) have identified CVI dermal fibroblasts as an important target for leukocyte-derived TGF-β1, and established a link between CVI progression and increased tissue levels of TGF-β1, MMP2 activity and decreased TGF-β1 induced mitogenic responses of fibroblasts [ 4 , 15 , 120 , 129 , 130 ]. Moreover, two other studies on CVI induced dermal changes suggested a connection between TGF-β1 signaling and cellular senescence [ 130 , 131 ]. It was also proposed that a molecular mechanism in which the persistent venous hypertension (via pressure mediated mechanotransduction) could stimulate Ras production, which in turn would activate MAPK/Erks, and hence inhibit TGF-β1 regulated matrix contraction (resulting in prolonged wound healing) [ 130 ].…”
Section: The Role Of Tgf-β1 Signaling Pathways In Vessel Wall Pathmentioning
confidence: 99%